2023
DOI: 10.3390/su15086765
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing through Social Media Platforms in the Silicon Age

Abstract: While making an appeal to the social exchange theory, self-determination theory and the uses and gratification theory of motivation, the study seeks to investigate the efficacy of social media platforms in promoting knowledge sharing in contemporary times, which are marked by widespread digital transformation and knowledge-driven governance. Through a PLS-based structural equation modelling performed on a dataset obtained from 450 business professionals working at disparate managerial levels in diverse organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 127 publications
0
8
0
1
Order By: Relevance
“…Yaqub and Alsabban showed that social media allows for informal communication, so it can help break down silos and significantly increase knowledge sharing within an organization. However, they also found that the relationship between social media use and knowledge sharing was moderated by a number of factors, including employee motivation and technical skills [27].…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Yaqub and Alsabban showed that social media allows for informal communication, so it can help break down silos and significantly increase knowledge sharing within an organization. However, they also found that the relationship between social media use and knowledge sharing was moderated by a number of factors, including employee motivation and technical skills [27].…”
Section: Knowledge Managementmentioning
confidence: 99%
“…The interconnectedness facilitated by technology creates a dynamic and inclusive environment where knowledge is not confined to textbooks but is a collaborative and evolving entity shaped by the contributions of diverse learners. As we embrace the digital era, the synergy between technology and knowledge sharing is poised to redefine the landscape of education, making learning more accessible, engaging, and meaningful for members of learning communities (Pang et al 2020;Zafar Yaqub and Alsabban 2023;Naeem 2019;Arsenijevi et al 2011;Huang et al 2023). In the following section, we provide a list of identified technologies that can be used for supporting knowledge sharing within learning communities.…”
Section: Identified Technologies For Supporting Knowledge Sharing In ...mentioning
confidence: 99%
“…The study by [53] indicates that using social media platforms could significantly boost knowledge sharing, but only if employees are incentivized to share knowledge with their colleagues, as well as to be computer-aware and use social media platforms. The growing use of social media to facilitate information sharing and ensure its broad dissemination among individuals, communities, and societies that use social media technologies generates a virtual space that encourages knowledge-sharing activities [18].…”
Section: The Use Of Smps For Knowledge Sharingmentioning
confidence: 99%